2020
DOI: 10.3390/su12083106
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical and Quality Assessment of Groundwater Resources in Al-Madinah City, Western Saudi Arabia

Abstract: Fifty-four groundwater samples were collected from Hamra Alasad in Al-Madinah City. The chemical and microbial characteristics of the samples were analyzed and compared with their respective standards. The results revealed that 90.7% of the samples showed higher amounts of NO3. However, 59.3% of the samples were found unfit for irrigation purposes due to a high salinity hazard. Most of the groundwater samples were highly saline, yet no sodicity hazards were anticipated as predicted by sodium adsorption ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The weighted mathematical model (IWQ1) referred to by the researchers (Agyemang, 2020;Alghamdi et al, 2020) was used and this model was applied using eleven criteria (as shown in Table 2) to assess water quality and the water quality index was calculated. (WQI) according to the following four equations:…”
Section: Calculating Of the Water Quality Index (Iwqi (mentioning
confidence: 99%
“…The weighted mathematical model (IWQ1) referred to by the researchers (Agyemang, 2020;Alghamdi et al, 2020) was used and this model was applied using eleven criteria (as shown in Table 2) to assess water quality and the water quality index was calculated. (WQI) according to the following four equations:…”
Section: Calculating Of the Water Quality Index (Iwqi (mentioning
confidence: 99%
“…The high salinity is observed for groundwater in both aquifers. The high salinity percentage may be attributed to either dissolved salts from evaporation ponds or anthropogenic activities associated with irrigation return flow and bottled water treatment factories that discharge saline water into the aquifer [20,31,33]. Consequently, an integrated approach for reconstructing and characterizing the sub-surface hydrostratigraphy at the scales of the main aquifer systems and identifying the aquifer hydraulic parameters are essential for planning future sustainable developments.…”
Section: Methodsmentioning
confidence: 99%
“…Two buried wadis lie underneath the Rahat volcanic area with alluvial deposit thickness exceeding 50 m. The average thickness of the alluvial unit associated with the aquifer buried underneath this area varies from 15 m to ~40 m (maximum thickness in the center of the wadi Alhamd: ~50 m) [30]. The average annual input and output from the sub-basaltic alluvium aquifers are about 2.95 × 10 7 m 3 and 4.05 × 10 7 m 3 , respectively, reflecting a shortage of 1.1 × 10 7 m 3 , causing a decline in the groundwater levels up to 0.1 to 0.15 m/month [31]. The upper layer is an aquitard (thickness: 1-20 m) that extends over Al-Madinah City and is formed mainly from impervious clay and silty clay.…”
Section: Hydrogeologymentioning
confidence: 99%
“…Furthermore, using the IDW tool of Arcgis software version 10.2 (ESRI 1999), the spatial distribution of the estimated WQI values in the Essaouira basin was obtained. The model of the Irrigation Water Quality Index (IWQI) was created as a practical hydrogeological tool for assessing the overall quality of irrigation groundwater [61,62], as amended by Verma [63]. As shown in Table 3, eleven factors were used in the research region to assess water quality for irrigation purposes.…”
Section: Analytical Techniques and Groundwater Samplingmentioning
confidence: 99%
“…As shown in Table 3, eleven factors were used in the research region to assess water quality for irrigation purposes. Each attribute is given a weight based on its relative importance [61,62,64]. Because of its significance and influence on plant growth and soil quality, electrical conductivity, for example, is given a weighting of five.…”
Section: Analytical Techniques and Groundwater Samplingmentioning
confidence: 99%